Network disruption detected in IE (Ireland) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Ireland. Data sourced from IODA.
Network Disruption Incident ID: IE-2026-0001. Severity: critical. Confidence: 75%